2013
DOI: 10.1021/bm400177q
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Stability and Serum-Resistance of Polyglutamate Polyelectrolyte Brushes/Nuclear Factor-κB p65 siRNA Polyplex Enhance the Apoptosis and Efficacy of Doxorubicin

Abstract: Short interfering RNAs (siRNAs) as chemotherapeutic RNAi agents hold great promise for a significant improvement in cancer therapy. Despite the promise, effective transport of siRNA with minimal side effects remains a challenge. The common problem associated with the low delivery efficiencies of current polycation-based gene delivery systems is their low stability in the presence of salt and serum. In the present study we developed the polyglutamate derivatives (PGS) polyelectrolyte brushes for NF-κB p65 siRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Polyelectrolyte complex (PEC) nanoparticles have attracted more attentions due to their wide merits as drug carriers, and they are suitable for loading some charged drug molecules such as DNA and proteins with high loading efficiencies. The drug releases can be controlled by pH and ionic strength (Li et al, 2011;Zhao et al, 2013;Tang et al, 2003;Teng et al, 2013;Rajkumar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Polyelectrolyte complex (PEC) nanoparticles have attracted more attentions due to their wide merits as drug carriers, and they are suitable for loading some charged drug molecules such as DNA and proteins with high loading efficiencies. The drug releases can be controlled by pH and ionic strength (Li et al, 2011;Zhao et al, 2013;Tang et al, 2003;Teng et al, 2013;Rajkumar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Zhao et al reported siRNA/PEI (25 kDa) polyplexes greater than 1 µm in diameter following a 1 h incubation in physiological saline (150 mM NaCl). [25] In the presented studies, all polyplexes retained small sizes that were below the 200 nm threshold for endocytic uptake. [26] Based on the relative stability of the polyplex structures and the minimal increase in D H , these studies suggested that the PEG block formed a protective corona following polyplex formation to resist both salt-induced aggregation and protein adsorption.…”
Section: Physical Characterization Of Polyplexes Formed With Mpeg-b-pmentioning
confidence: 82%
“…mPEG-b-P(APNBMA) 23.6 provided enhanced siRNA binding, to form salt-stable copolymer-based polyplexes that resisted aggregation following incubation in PBS, as compared to substantial growth for siRNA/PEI polyplexes (to > 1 µm in diameter). [25] Serum exposure of siRNA/mPEG-b-P(APNBMA) 23.6 polyplexes indicated tight association, in contrast to poly(L-lysine)-based polyplexes that showed > 90% siRNA dissociation following 1 h of serum incubation. [5b] Delivery of mPEG-b-P(APNBMA) 23.6 polyplexes to NIH/3T3 cells facilitated > 80% cellular uptake compared to 40% for Lipofectamine lipoplexes, and cytoplasmic release of siRNAcontaining polyplexes within 3 h of polyplex exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Once taken up by the cells, cationic nanocarriers are able to destabilize and escape from the endosomal membrane by the proton-sponge and umbrella effects, and then they can release nucleic acids into the cytoplasm [36]. Although cationic nanocarriers promote cellular uptake in intracellular environments, the experience accumulated over the last years has revealed some important limitations, especially regarding instability due to interactions with extracellular matrix proteins and complement proteins in blood plasma [37], that exacerbate, soothe, or mask the effects of the delivered nucleic acids [38,39].…”
Section: Anti-fouling Pegylated Surfaces Of Nanocarriers Prolong Bloomentioning
confidence: 99%